The Great Recession or progressive energy policies? Explaining the decline in US greenhouse gas emissions forecasts. Issue 3 (3rd March 2016) - Nelson, Hal T.; von Hippel, David; Peterson, Tom; Garagulagian, Roman
Abstract : This paper evaluates the causes of the 23% decline in 2030 US greenhouse gas emissions forecasts between 2007 and 2011. Dynamic regression modeling predicts that the Great Recession contributed to about 67% of the 2008–2009 emissions decline, but then fell to about an 18% share for the 2030 emissions forecast. An analysis of electricity generation forecasts show that switching from coal to gas contributed only 6% to the total 2030 decline. In contrast, regulatory impact assessments and policy analysis showed that state and federal policies were responsible for 46% of the 2030 decline in emissions.